Carrying Capacity of Agricultural Land in Disaster-Prone Areas of Land Movement at Karangsambung-Karangbolong Geopark. Issue 1 (1st September 2022) - Harini, R; Susilo, B; Pangaribowo, E H; Ariani, R D
Abstract: A disaster-prone area is an area that has a high level of vulnerability to potential threats to life, welfare, and residents' assets when a disaster occurs. Land damage due to landslides has the potential to reduce the region's ability to supply human resources, especially in the agricultural sector. This condition has an impact on decreasing the carrying capacity of agricultural land. This study aimed to analyze the distribution pattern and carrying capacity of agricultural land in the disaster-prone area of the Karangsambung-Karangbolong Geopark. Data sources used were secondary and primary data. The secondary data were obtained from the Central Bureau of Statistics of Kebumen Regency and the Regional Disaster Management Agency of Kebumen Regency. The primary data were obtained from observation and in-depth interviews. Data analysis was carried out in a quantitative descriptive manner. The carrying capacity of agricultural land was obtained using the Odum-Howard-Isaard agricultural land productivity approach with a classification based on Decent Living Needs (DLN). The results showed that the available land carrying capacity (LCC), especially rice fields, was lower than the farmers' needs thus the LCC value was a deficit. In geopark areas that had low LCC and was indicated by low levels of agricultural production could not be able to carry out food self-sufficiency. The carrying capacity of agricultural land in disaster-prone areas can be increased through policies to prevent land conservation and intensify agricultural land processing.